Digital Sebagai Sarana Promosi Usaha Mikro Pada Pelaku Usaha di Desa Uraur - Josef R. Pattiruhu; Agusthina Risambessy; Victor E. Huwae; Steven Sialia (Community Engagement and Emergence Journal (CEEJ), 2024)
Uraur Village is the entrance to Honitetu. Indigenous Peoples who live in Uraur Village have the same freedom as other Honitetu Indigenous Peoples to access their customary forests and take their food needs from there. At the traditional community level, the important role of women in traditional institutions or what is commonly referred to as Saniri can be seen. Most of the people in Uraur village work as farmers and laborers. Uraur village has very fertile and attractive natural potential which can provide opportunities for each individual to be able to do business, but in reality the community, people far prefer to become civil servants rather than being business actors, even if there are business actors, it is not small compared to the number of people in the community. The method used in this activity is counseling or lecture which aims to provide an understanding of digital technology as a means of promoting the results of creative efforts by business actors. The result of this activity is the absorption of knowledge and the formation of a complete understanding by business actors through the material presented so that partners can change their mindset and shift traditional marketing methods to digital marketing methods so that businesses by micro business actors survive so that business actors are able to contribute to the creative economy.